Effect of gambir catechins on cholesterol levels of mice hypercholerolemia - Anggaraini, Mita; Yuniarti, Elsa; M, Des; Ramadhani, Sari (International Journal on Health and Medical Sciences, 2023)
Hypercholesterolemia is a condition characterized by increased level of cholesterol in the blood exceeding the normal threshold. Gambir (Uncari gambir Roxb.) contains chemical compounds, namely flavonoid, specifically catechin. Catechin in gambir has the potential to increase fat metabolism therefore it has the potential to reduce cholesterol level in the body of mice. The purpose of this study is to determine the effect of gambir catechin on cholesterol levels in hypercholesterolemic mice. The study is an experiment with a Completely Randomized Design (CRD) with two control groups and three treatment groups those are K negative was not given treatment, K positive was induced by simvastatin after induction of a high-fat diet, P1, P2 and P3 were induced by catechin with different concentrations of 50%, 80% and 90% after being induced by a high-fat diet. Cholesterol level was checked with Easy touch GCU. Data was analyzed by One Way of Variance (ANOVA) followed by 5%-degree DMRT test. The result shows that gambir catechin has the effect (p<0.05) on reducing cholesterol level in hypercholesterolemic patients. The most effective using of catechin with the level of concentration of catechin is at 90%.